Establishing Global School Feeding Program Targets: How Many Poor Children Globally Should Be Prioritized, and What Would Be the Cost of Implementation? - Lesley J. Drake; Nail Lazrak; Meena Fernandes; Kim Chu; Samrat Singh; David Ryckembusch; Sara Nourozi; Donald A. P. Bundy; Carmen Burbano (Frontiers Media S.A., 2020)
The creation of Human Capital is dependent upon good health and education throughout the first 8,000 days of life, but there is currently under-investment in health and nutrition after the first 1,000 days. Working with governments and partners, the UN World Food Program is leading a global scale up of investment in school health, and has undertaken a strategic analysis to explore the scale and cost of meeting the needs of the most disadvantaged school age children and adolescents in low and middle-income countries globally. Of the 663 million school children enrolled in school, 328 million live where the current coverage of school meals is inadequate (<80%), of these, 251 million live in countries where there are significant nutrition deficits (>20% anemia and stunting), and of these an estimated 73 million children in 60 countries are also living in extreme poverty (<USD 1.97 per day). 62.7 million of these children are in Africa, and more than 66% live in low income countries, with a substantial minority in pockets of poverty in middle-income countries. The estimated overall financial requirement for school feeding is USD 4.7 billion, increasing to USD 5.8 billion annually if other essential school health interventions are included in the package. The DCP3 (Vol 8) school feeding edition and the global coverage numbers were launched in Tunis, 2018 by the WFP Executive Director, David Beasley. These estimates continue to inform the development of WFP's global strategy for school feeding.